Learning of Cross-Cultural Based Writing Skill in The English Camp Program (ECP) of English Education Department - Mohammad Hafidz; Maulana Yusuf Aditya (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2019)
Learning of cross cultural based writing skills is the process of conveying different cultural values to be consciously understood and presented in written text. The purpose of the research is to convey and apply the new culture of various national capitals in learning writing skills. This study used a qualitative descriptive approach with a case study design, the data were collected directly by observingÂ the activities of ECP (English Camp Program). in Mojokerto. Then, researcher analyzed the dat using content analysis of social treatment withÂ reducing, presenting data and drawing conclusions.The result is cross-cultural based learning makes ECP participants easy to write because of the availability of a variety of theoretically and practically references. Cross-cultural based learning is not a psychological problem but a very interesting scientific study to be applied into real life. Cross-cultural understanding is the main element in producing comprehensive writing skill.